Primiparous understandment on breastfeeding - descriptive quantitative study - Diana Soares de Azevedo; Ana Cândida Serafim dos Reis; Lydia Vieira Freitas; Thaís Marques Lima; Priscila Bomfim Costa; Patrícia Neyva da Costa Pinheiro; Ana Kelve de Castro Damasceno (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Aim: this study aimed to analise the puerperals' understandment on breastfeeding e its caracteristics. Methood: descriptive study with quantitative aproach, which took place in the maternity school Assis Chateubriand between november of 2006 and january of 2007 with 252 puerperal interns. Results: most women were between the ages of 19 and 25 (48,8%), had gone to school for 8 years or more (59,5%), lived with theirs partners (75,8%) and were housewifes (73%). Most of them were going throught their first pregnancy (86,5%), went through seven or more pre-natal apointments (48,8%), prefered vaginal delivery (69,8%), believed that the best moment to iniciate breastfeeding is right after delivery (51,1%) and said had received information on breastfeeding (86,9%). Regarding their understandement on breastfeeding, they know that maternal diseases may impose it (31,7%), refered to liquid ingestion as a possible lactine prodution estimulate (51,1%) and pointed out that massages (26,2%) and milking (28,6%) ease the mamalian shrinkcage. Acknowledgements: many issues still need to be improoved to assure breastfeeding carries on until the recommended period and with success.